Privileged access and rural vulnerabilities: Examining social and environmental exploitation in bioenergy development in the American Midwest. (October 2016) - Kulcsar, Laszlo J.; Selfa, Theresa; Bain, Carmen M.
Abstract: Negative environmental externalities typically emerge in rural areas due to urban centers' privileged access to the rural hinterland for economic activities related to the extraction and processing of natural resources. Less attention has been given to those cases when both the promotion of economic activities and their consequential inequalities are driven from within rural communities themselves. Privileged accounts within communities naturalize environmental concerns and divert attention from the inequalities associated with the costs and risks of economic development. Within this context, it is important to examine local perceptions, framings, and power structures that create and perpetuate asymmetries in access to natural resources for economic development and the local vulnerabilities they create. Drawing on Freudenberg's theory of privileged access and privileged accounts, this paper examines the promotion and development of biofuels plants in the rural American Midwest. Here, proponents of biofuels development argued that biofuel facilities were ideally suited to local conditions, where large-scale corn production, the main biomass input, is extensive. Drawing on data from surveys of six case study communities in rural Kansas and Iowa, augmented by in-depth stakeholder interviews, we discuss the local support towards biofuels production in the context of environmental concerns. The results indicate significant rural community support despite evidence that the contribution of biofuels production to local livelihoods was minimal. We show how these privileged accounts create largely unified support locally for biofuels production and quiescence concerning the disproportionality of benefits, potential environmental harms and long term development challenges.